Effect of heat treatment on thermal stability of Ti40 alloy - 辛社伟 赵永庆 曾卫东 (Transactions of Nonferrous Metals Society of China, 2007)
Five new heat treatment processes were designed, which were divided into three groups by their characteristics. The microstructures and mechanical properties of the alloy after the five heat treatments and thermal exposure at 500, 550℃ for 100 h were tested. The results indicate that a little differences exist in the performance of mechanical properties at room-temperature after the five heat treatments, and the thermal stability is the key factor for determining heat treatment process. Among the three groups of heat treatment processes, the best thermal stability is achieved after the first group of heat treatment. After annealing treatment at intermediate temperature, some defects and uneven grain boundaries are remained, which leads to the reduction fractions of precipitations on unit grain boundary and the harmful effect of precipitations on grain boundary is weakened. The process of annealing at 650 ℃for 4 h is recommended the best heat treatment process for Ti40 alloy.